Self-oriented affective empathy is associated with increased negative affect - Hülsemann, Mareike; Kaurin, Aleksandra; Kollmann, Bianca; Chmitorz, Andrea; Ahrens, Kira F.; Schenk, Charlotte; Plichta, Michael M.; Lutz, Beat; Basten, Ulrike; Fiebach, Christian J.; Kalisch, Raffael; Lieb, Klaus; et al. (Scientific reports, 2025)
An increasing body of research suggests that empathic traits at high levels may predict negative affectivity. Here, we investigate the combinatory and differential role of affective (personal distress, empathic concern) and cognitive (perspective taking) facets of empathy for their contribution to negative affectivity in two general population samples (N1 = 259, N2 = 938). A latent profile analysis revealed four combinatory groups of affective and cognitive empathic facets (i.e., high affective high cognitive [A+/C+], high affective low cognitive [A+/C−], low affective high cognitive [A−/C+], low affective low cognitive [A−/C−]). These groups were differentially associated with negative affectivity, showing that greater affective empathy was associated with increased negative affect. Moreover, moderation and subsidiary simple slopes analyses demonstrated that self-oriented affective empathy (personal distress) was generally positively associated with depression and anxiety. In case of depressive symptomatology, this correlation was lower under circumstances of high cognitive empathy, but only in the larger, second sample. Other-oriented affective empathy (empathic concern) was not related to negative affect. Our findings suggest that enhanced self-focused affective empathy may be associated with exaggerated involvement in the emotional experience of others, with the potential to reduce the negative correlation of accurate emotion recognition with negative affect.